Reward and organizational commitment "case study at University of Malaya Centre for continuing education (UMCCed) - Norhasliza, Ibrahim (2019)
Rewards play a crucial role for organizational outcomes and employees’ satisfaction towards organizations. This study investigates the relationship between rewards and organizational commitment. Using a self-administered questionnaire, this study involved 97 employees who work at University of Malaya Centre for Continuing Education (UMCCed). The data was analyzed using Statistic Package for Social Science (SPSS) version 17 for descriptive and inferential analysis. The findings of this study showed that they offered both extrinsic (salary, bonus and promotion) and intrinsic (praise, recognition and genuine appreciation) rewards to their employees. Hierarchical regression analysis revealed that these two types of rewards are important for organizational commitment. These findings suggest that UMCCed must implement the several rewards which are very important for the staff to stay at UMCCed.